2008
DOI: 10.4238/vol7-4gmr485
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and comparison of clinicohematological parameters and molecular and cytogenetic response of two Bcr/Abl fusion transcripts

Abstract: ABSTRACT. Different forms of p210 are produced by alternative splicing, namely b2a2 and b3a2. There have been many contrasting data establishing a relationship between the two Bcr/Abl transcripts and platelet counts and also response to treatment. However, the data published to date have been on a small group of patients. The aim of the present study was to determine whether there was any difference between clinical and hematological parameters at diagnosis between the two Bcr/Abl fusion transcripts in our pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 25 publications
6
40
3
3
Order By: Relevance
“…22 Furthermore, patients with the e14a2 transcript were found to have a higher level of 5'ABL deletions as an additional chromosomal abnormality, when compared to e13a2-expressing patients. 7 Other studies found no correlations with the above, or with any other clinical or hematologic parameters. .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…22 Furthermore, patients with the e14a2 transcript were found to have a higher level of 5'ABL deletions as an additional chromosomal abnormality, when compared to e13a2-expressing patients. 7 Other studies found no correlations with the above, or with any other clinical or hematologic parameters. .…”
Section: Discussionmentioning
confidence: 92%
“…7 The e14a2 transcript has been correlated with a higher platelet count in both adults 8,10 and children. 21 Additionally it has been associated with a longer chronic phase and survival, possibly related to the less aggressive course of chronic phase in patients with this transcript type.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Regarding hematologic characteristics at diagnosis, the observation of higher platelet counts in the e14a2 group must now be considered in the light of reports to the contrary over the past two decades. 4,7,8 There has still been no evaluation of distinct disease characteristics and the prognostic implications of different p210 BCR-ABL1 transcript types in a larger data set of CML patients on imatinib treatment. In this study, we analyze the long-term molecular, cytogenetic, and clinical outcome of 1105 chronic-phase CML patients receiving an imatinib-based treatment within the randomized German CML Study IV.…”
Section: Introductionmentioning
confidence: 99%